Les groupes binominaux de type N2’s N1, N1 of N2 et N2N1 - Evelyne Chabert (Corela)
The paper deals with N2’s N1/N1 of N2/N2N1 alternation. It seeks to evaluate the validity of Adamczewski’s model, which proposes that the difference lies in the degree of ‘fusion’ between the referents of N1 and N2.An analysis of occurrences taken from the TLD corpus shows that Adamczewsi’s theory fails to account for the alternation and that, more generally, it exhibits the main invalidating features of a dysfunctional model: lack of universality, epistemic circularity, irrefutability and lack of predictive power. An alternative explanation of the alternation under study is put forward. It rejects the existence of a semantic invariant, and proposes that it is the function of N2 – either determinative or modifying – that triggers the speaker’s preference for one structure over the other two. It also ventures the hypothesis that compounds are gaining ground over genitive NPs, a process in line with the diachronic evolution that has gradually turned English into an analytic language.